2022
DOI: 10.1128/spectrum.02011-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waterlogging on Soybean Rhizosphere Bacterial Community Using V4, LoopSeq, and PacBio 16S rRNA Sequence

Abstract: Soybeans are important oil-bearing crops, and waterlogging has caused substantial decreases in soybean production all over the world. The microbes associated with the host have shown the ability to promote plant growth, nutrient absorption, and abiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Megamonas rupellensis, Bacteroides plebeius, and Bacteroides coprocola were the dominant species in both sequencing methods. Previous studies have reported that the community profiles using synthetic long-read sequencing technologies (LoopSeq) and PacBio CCS from the same fecal samples were comparable ( Yu et al, 2022 ). Compared to PacBio 16S sequencing, 16S-FAS-NGS offered high fidelity species identification but reduced sequencing prices, which was an attractive technology with species-level resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Megamonas rupellensis, Bacteroides plebeius, and Bacteroides coprocola were the dominant species in both sequencing methods. Previous studies have reported that the community profiles using synthetic long-read sequencing technologies (LoopSeq) and PacBio CCS from the same fecal samples were comparable ( Yu et al, 2022 ). Compared to PacBio 16S sequencing, 16S-FAS-NGS offered high fidelity species identification but reduced sequencing prices, which was an attractive technology with species-level resolution.…”
Section: Resultsmentioning
confidence: 99%
“…The total rhizosphere soil of total plants of RS and RSSI plant treatments was removed at 30 dpi by shaking the root manually; meanwhile, the basal soil (BS, non-rhizosphere soil) was collected as the control [ 57 ]. Furthermore, the soil samples were mixed and used for three separate determinations of soil chemical properties, soil enzymes and soil microorganisms, and metabolite profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Plant-associated microbial communities are well known for their impact on the ecology and evolution of their host ( Trivedi et al, 2020 ; Malacrinò et al, 2022a ). The structure of plant microbiomes largely differentiate within the same plant (e.g., between roots, leaves, fruits, flowers, seeds), and within the same compartment (e.g., different tissues within the same organ; Abdelfattah et al, 2016 ; Dastogeer et al, 2020 ; Trivedi et al, 2020 ), and it is influenced by several factors, including soil ( Zarraonaindia et al, 2015 ; Malacrinò et al, 2021a ), herbivores ( French et al, 2021 ; Malacrinò et al, 2021a , b ; Frew, 2022 ), pathogens ( Ginnan et al, 2020 ; Wen et al, 2020 ; Ewing et al, 2021 ), and abiotic stresses ( Vescio et al, 2021 ; Yu et al, 2022 ). Despite the great deal of research in this field, we still know little about the rules that govern the assembly of plant microbiomes.…”
Section: Introductionmentioning
confidence: 99%